The Analysis of Education Programmes of Protected Areas and Possibilities of Using Them in Nonformal Learning - Klimienė, Asta; Klimas, Ramutis (Pedagogika, 2015)
The learning in non-traditional environment can help to identify attractive activities, gain for each necessary social, and cultural competency. Non-formal education can help solve many problems in protected areas. In mostly all protected areas in Lithuania are educational activities – and this is one of aim of this institutions and also one of the educational components. Recently, but both the pupils and the public interest in science education has decreased. The protected areas organized various educational activities but by the research data 29 % respondents are not visited protected areas and not interested in them. The analysis of proposed educational activities in protected areas and opinions of the respondents, it is noted that the most popular educational activity in Lithuania is the tour (51.3 %). But sometimes the tour is called education. Only the Curonian Spit National Park carried out a study educational project with a local school, and only in Samogitia (Žemaitija) National park is the eco-education center.